2018
DOI: 10.3390/ijerph15071410
|View full text |Cite
|
Sign up to set email alerts
|

Misophonia in Singaporean Psychiatric Patients: A Cross-Sectional Study

Abstract: Misophonia, also known as selective sound sensitivity syndrome, is a condition characterized by strong dislike of specific sounds with accompanying distressing reactions. To date, misophonia is still poorly understood. This study aimed to identify factors associated with severity of misophonic symptoms in Singaporean psychiatric patients. Ninety-two psychiatric patients were recruited from a large teaching hospital in Singapore in a cross-sectional study. Socio-demographics, severity of depression, anxiety and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
96
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 12 publications
4
96
0
3
Order By: Relevance
“…Questions 3, 5, 10, 13, 16, 17 and 21formed the depression subscale. The total depression subscale score was divided into normal (0-9), mild depression (10)(11)(12), moderate depression (13)(14)(15)(16)(17)(18)(19)(20), severe depression (21)(22)(23)(24)(25)(26)(27), and extremely severe depression (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). Questions 2,4,7,9,15,19, and 20 formed the anxiety subscale.…”
Section: Survey Developmentmentioning
confidence: 99%
“…Questions 3, 5, 10, 13, 16, 17 and 21formed the depression subscale. The total depression subscale score was divided into normal (0-9), mild depression (10)(11)(12), moderate depression (13)(14)(15)(16)(17)(18)(19)(20), severe depression (21)(22)(23)(24)(25)(26)(27), and extremely severe depression (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). Questions 2,4,7,9,15,19, and 20 formed the anxiety subscale.…”
Section: Survey Developmentmentioning
confidence: 99%
“…Mental health was measured using the Depression, Anxiety and Stress Scale-21 items (DASS-21) [15].The DASS has been demonstrated to be a reliable and valid measure for assessing mental health in the Chinese population [6,16,17], and it has been applied in studies related to the SARS outbreak [18]. The DASS-21 is a set of three self-report scales designed to measure the emotional states of depression, anxiety, and stress.…”
Section: Psychological Impact and Mental Healthmentioning
confidence: 99%
“…The DASS-21 obtained high reliabilities in the Italian validation study, with Cronbach's alphas of 0.74, 0.82, and 0.85 for the Anxiety, Depression, and Stress subscales, respectively; Cronbach's alpha for the total scales was 0.90. In the Lovibond and Lovibond version of the DASS-21 [19], the subscales are scored as follows: normal (0-9), mild (10-12), moderate (13)(14)(15)(16)(17)(18)(19)(20), severe (21-27), and extremely severe (28-42) for Depression; normal (0-6), mild (7-9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), and extremely severe (20-42) for Anxiety; and normal (0-10), mild (11)(12)(13)(14)(15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25)(26), severe (27-34), and extremely severe (35-42) for Stress.…”
Section: Psychological Impact and Mental Healthmentioning
confidence: 99%
“…People with misophonia while being exposed to certain auditory triggers experience strong, immediate, unwanted emotions and physiological reactions such as increased heart rate, sweating, and muscle tension. The dominant, but not exclusive, emotions related to misophonia are anger, disgust, extreme irritation, and anxiety [3,5,6]. In contrast to the less-discussed phonophobia [7], misophonia is not associated with experiencing fear of the sound while it is occurring [8,9], excluding it from classification as a phobia.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most aversive triggers are sounds made by human mouths or noses, such as chewing, breathing sounds, lip-smacking, crunching, or sniffing. Some researchers [6] noted that the sound of a baby crying orhigh-pitched voices can also trigger misophonic reactions; however, the study by Kumar et al [10] showed that these kinds of sounds evoke significantly different reactions on psychophysiological and neuropsychological levels than do sounds related to eating. They found that in people with misophonia, sounds of eating, breathing, or drinking (trigger sounds) are related to abnormal activation of the anterior insular cortex (AIC) and abnormal functional connectivity of this structure with brain areas responsible for emotion processing and regulation.…”
Section: Introductionmentioning
confidence: 99%